White, Robin R., (2025). Generative artificial intelligence tools in journal article preparation : A preliminary catalog of ethical considerations, opportunities, and pitfalls. Jds Cummunications, 6: 452-457. - khanthachai, natthaphon (KASEM BUNDIT JOURNAL, 2025)
PURPOSES: To present a guideline for application of generative artificial intelligence tools in journal article preparation, including ethical considerations, opportunities, and pitfalls. METHODS: Review and critical interpretation approaches on application of generative artificial intelligences tools in journal article preparation. RESULTS: Generative artificial intelligence tools such as ChatGPT is very helpful in quality journal article preparative. And yet, they should be applied with careful practices and should not be a substitute of human in peer review. THEORETICAL/POLICY IMPLICATIONS: Authors and editors or academic journals could carefully apply generative artificial intelligence tools in quality journal article preparation.